2015
DOI: 10.5606/archrheumatol.2015.5445
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Spa Therapy on Pain and Quality of Life in Patients With Chronic Mechanical Neck Pain

Abstract: Objectives: This study aims to evaluate the efficacy of spa therapy on pain and the quality of life in patients with chronic mechanical neck pain. Patients and methods:Seventy patients who applied to our outpatient clinic with chronic mechanical neck pain lasting for 12 weeks were included in the study. Patients were randomized either to spa therapy group (7 males, 28 females; mean age 43.08±9.76 years; range 26 to 66 years) or to exercise therapy group (5 males, 30 females; 46.45±9.65 years; range 27 to 65 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
1
1
0
1
Order By: Relevance
“…In conclusion, Spa therapy + HE were shown to be more effective in reducing pain and increasing functionality in the short term compared to HE. [ 28 ] In our study, in accordance with these studies, thermotherapy administration with heated MP and HP treatments was shown to reduce pain, increase functionality and improve QoL in the short term in patients with CNP.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In conclusion, Spa therapy + HE were shown to be more effective in reducing pain and increasing functionality in the short term compared to HE. [ 28 ] In our study, in accordance with these studies, thermotherapy administration with heated MP and HP treatments was shown to reduce pain, increase functionality and improve QoL in the short term in patients with CNP.…”
Section: Discussionsupporting
confidence: 79%
“…There are many studies in the literature about the efficacy of thermotherapeutic treatments for CNP. [ 7 , 27 , 28 ] A randomized-controlled study assessing the efficacy of naturopathic administrations in addition to local thermotherapy and acupuncture for CNP observed that complementary thermotherapy and acupuncture administered to patients supported reductions in pain and improvements in functionality. [ 27 ] A randomized-controlled study by Cramer et al[ 7 ] compared the efficacy of heated MP with a treatmentfree control group for chronic mechanical neck pain (CMNP).…”
Section: Discussionmentioning
confidence: 99%
“…Afyonkarahisar doğuyu batıya, kuzeyi güneye bağlayan yolların kavşak noktasında bulunan ve termal kaynaklar yö- (20); farklı sular ve tekniklerin, boyun ağrıları ve buna bağlı dizabiliteyi azalttığı ve fonksiyonel kapasiteyi, yaşam kalitesini, boyun eklem hareketliliğini, dengeyi ve ruh halini iyileştirdiğini, relaksasyonu artırdığı bildirilmiştir. Bizim kliniğimizde boyun ağrılı hastalarda daha önceden yaptığımız bir çalışmada egzersiz tedavisine spa tedavisi eklenmesinin sadece egzersize göre, tedaviden sonraki erken dönemde ağrıyı azaltmada ve fonksiyonel kapasiteyi iyileştirmede sadece egzersiz tedavisine göre daha etkili olduğunu bulmuştuk (21). Yine ülkemizden bir çalışmada, kronik boyun ağrılı hastalarda balneoterapi ve fizik tedavi kombinasyonu, tek başına fizik tedaviye göre ağrı ve dizabiliteyi azaltmada ve yaşam kalitesini artırmada daha üstün bulunmuştur (22).…”
Section: Discussionunclassified